Existence of Adaptively Stable Sunspot Equilibria Near an Indeterminate Steady State - George W. Evans; Seppo Honkapohja (Center for Economic Studies and ifo Institute (CESifo), 2001)
We examine the nonlinear model Xt = Et F(xt+1) . Markov SSEs exist near an indeterminate steady state, X = F(X), provided F(X)> 1. We show that there exist Markov SSEs that are E-stable, and therefore locally stable under adaptive learning, if F(X)< -1.
Keywords: 330; Indeterminacy; learnability; expectational stability; endogenous fluctuations